Does Exposure to Unawareness Affect Risk Preferences? A Preliminary Result - Burkhard C. Schipper; Wenjun Ma (University of California, Department of Economics, 2017)
One fundamental assumption often made in the literature on unawareness is that risk preferences are invariant to changes of awareness. We study how exposure to unawareness affects choices under risk. Participants in our experiment choose repeatedly between varying sure outcomes and a lottery in 3 phases. All treatments are exactly identical in phase 1 and phase 3, but differ in phase 2. There are five different treatments pertaining to the lottery faced in phase 2: The control treatment (i.e., a standard lottery), the treatment with awareness of unawareness of lottery outcomes but known number of outcomes, the treatment with awareness of unawareness of outcomes but with unknown number of outcomes, the treatment with unawareness of unawareness of some outcomes, and the treatment with an ambiguous lottery. We study both whether behavior differs in phase 3 across treatments (between subjects effect) and whether differences of subjects' behavior between phases 1 and phase 3 differs across treatments (within subject effects). We observe no significant treatment effects.
Keywords: C91; C92; D81; D87; 330; Unawareness; Awareness of unawareness; Risk aversion; Experiments